Systems and procedures study on Kamia Residence Hall - Marders, Joel; Salangad, Christine; Tiu, Daniel; Tupaz, Jovi Francis; Zarate, Ma. Therese Laarni (College of Engineering, 1991)
After having some transportation and access problems with our last site in our Methods Study, the group unanimously decided to have a site which was easily accessible and whose data sheets and other informations were more or less open to all. The ever-increasing number of students in the University prompted to us to reflect on how the "in campus" housing facilities were serving the welfare of the growing Diliman population. Majority of the us (3 out of 5) were "non-dormers" and we wondered what kind of life lurks in the vast abyss of the decade old abodes they call dormitories. This and other factors influenced us to try to discover what really goes beyond the outside facade. Kamia Residence Hall is one of the oldest dormitories for women students in the University of the Philippines campus. This forty-one year old dormitory for "upperclasswomen" was first known as the Women's South Dormitory when it was constructed in 1950. It is connected by a covered walk to another campus dormitory for women, the Sampaguita Residence Hall. Kamia Residence Hall is across the street from the College of Arts and Sciences and the Department of Zoology buildings.